Analysis of alternative selection for vertical clearance design under Tabalong Bridge of PT Adaro Indonesia - Regar, Diean Oktavian; Mursadin, Aqli (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
PT Adaro Indonesia is trying to adjust a vertical clearance under Tabalong Bridge 1 (unloaded) and Tabalong Bridge 2 (loaded) because the existing conditions still apply a minimum vertical clearance of 4 m. I t should be in accordance with latest Regulation of the Minister of Public Works No. 19/PRT/M/2011 that for vertical clearance above national road at least 5.1 m. This specification has not been met by the national road under the Tabalong 1 & 2 Bridges bec ause both bridges were built in the 90s. Therefore we need an engineering technique to overcome this. There are 2 alternative designs, namely lowering the elevation of the national road and increasing the elevation of the bridge’s upper structure to mitiga te oversized vehicles so as not to hit the lower structure of the Tabalong bridge. In determining the selection of the best alternative designs in this research is based on two (2) things, non financial criteria with Analytical Hierarchy Process (AHP) and financial criteria with Life Cycle Cost Analysis (LCCA)/Benefit Cost Ratio (BCR) method. This study uses a survey method by distributing questionnaires and interviews as a means of collecting primary data. In addition, previous research and consultant DED documents were used as a means of collecting secondary data. The AHP method is used to process primary data to produce a decision from a non financial aspect. While the LCC/BCR method is used to process secondary data to produce a decision from the financi al aspect . The results of the AHP analysis obtained that the synthesis value of the decision the option of lowering national roads was 85% and the bridge lifting option was 15% and the consistency ratio (CR) was 0.05 < 0.1. The consistency ratio below 0.1 shows that the questionnaire data from the respondents are consistent. The results of the analysis of Life Cycle Cost (LCC) obtained the option of lowering national roads where the LCC value is Rp. 44,877,651,669.27 more economical than the bridge lifting option. Then the results of the Benefit Cost Ratio (BCR) analysis obtained the option of lowering national roads with a BCR value of 2.33 > 1 and NPV = Rp. 43,442,264,804.34 > 1 means that the option lowering national roads is feasible. While the bridge li fting option is obtained by analyzing the value of BCR = 0.98 < 1 and NPV = option is not feasible to implement.